Exposure to second-hand smoke predicts breast cancer occurrence among Malaysian women - Ainaa Almardhiyah Abd Rashid,; Zunura’in Zahali,; Gan, Siew Hua; Bhavaraju Venkata Murali Krishna,; Sarimah Abdullah,; Sharifah Zahhura Syed Abdullah,; Hamid Jan Jan Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Breast cancer is the commonest type of cancer among Malaysian women. This study aimed to determine the associated factors for breast cancer occurrence among Malaysian women. A case-control study was conducted at primary cancer referral centre in the East Coast of Peninsular Malaysia from January 2014 to August 2015. Untreated breast cancer (n=55) were assigned as cases compared to healthy controls (n=58). Sociodemographic and reproductive data were collected using a standardized questionnaire while dietary data was obtained using validated diet history questionnaires (DHQ). Anthropometric assessments (weight, height, hip, waist circumference (WC) and body fat composition) were recorded. Overnight fasting venous blood samples were analysed for glucose levels, insulin, high sensitivity C reactive protein (hs-CRP), high molecular weight (HMW) adiponectin and lipid profiles. Simple logistic regression showed factors associated with breast cancer risk include age, lower education level, lower monthly household income and exposure to secondary smoke (sociodemographic factors), pulse rate, the use of more than one year of traditional medicine, systolic, and diastolic blood pressures (physical examination and reproductive factors) as well as WC, HDL cholesterol, TG, blood glucose, and sugar intake (nutritional status) were investigated. Multiple logistic regression showed factors associated with breast cancer risk included exposure to a second-hand smoke (OR=10.00, (95% CI: 2.42, 41.30)), low monthly household income (OR=18.05, (95% CI: 2.56, 127.10)) and high systolic blood pressure (OR=1.08, (95% CI: 1.04, 1.12)). Exposure to second-hand smoke, low monthly household income and high systolic blood pressures are predictors to breast cancer among Malaysian women.